Serial millisecond crystallography of membrane and soluble protein microcrystals using synchrotron radiation. (2017) - Martin-Garcia, Jose M.; Conrad, Chelsie E.; Nelson, Garrett; Stander, Natasha; Zatsepin, Nadia A.; Zook, James
No abstract available